Optimalisasi Pengembangan Diri Terkait Kewirausahaan Di Karang Taruna Parikesid: Optimization Of Self-Development Related To Entrepreneurship In Karang Taruna Parikesid - Shabana, Farah Nabila; Nabila, Ulima Nurin; Rahmadyah, Erza Noorhailiza; Wijanarko, Novita Sari; Hapsari, Novia Nanda Rizqy; Daniar, Sakinah; Yunanto, Taufik Akbar Rizqi (Universitas Muhammadiyah Sidoarjo, 2020)
This psychoeducation aims to help the PARIKESID youth group meet their needs, namely the need to optimize the self-development of youth in the SIDOSERMO area and to help the PARIKESID youth organization attract youth to participate in social activities and join the PARIKESID youth organization. Psychoeducation is carried out using Lecture, Audio Visual, Sharing, Game, Discussion, Pretest and Posttest learning methods, as well as Self-Reflection. The weak institutional management of the PARIKESID Youth Organization in optimizing the potential of its members is the most influential problem in the organization. Moreover, with the current growing power at Karang Taruna PARIKESID, this has made the younger generation around Sidosermo not see the importance of interaction in youth organizations